Comparison of pnicogen and tetrel bonds in complexes containing CX2 carbenes (X = F, Cl, Br, OH, OMe, NH2, and NMe2). (18th September 2019) - Lin, Hui; Meng, Lingpeng; Li, Xiaoyan; Zeng, Yanli; Zhang, Xueying
Abstract : The similarities and differences of pnicogen and tetrel bonds formed by carbenes CX2 with H3 AsO and H3 SiCN were investigated by carrying out ab initio calculations in association with topological analysis of electron density. Abstract : The similarities and differences of pnicogen and tetrel bonds formed by CX2 carbenes (X = F, Cl, Br, OH, OMe, NH2, and NMe2 ) with σ-holes of H3 AsO and H3 SiCN were investigated by carrying out ab initio calculations in association with topological analysis of electron density and energy decomposition analysis. The strength of the σ-hole interactions was found to be essentially related to the nature of the group IV/V atom and the substituent of the carbene. The interaction energies of the tetrel-bonded complexes were calculated to be more negative than those of the corresponding pnicogen-bonded complexes except for H3 SiCN⋯CF2 . In the formation of the complexes, the geometries of the H3 AsO⋯CX2 systems did not change much, while greater deformations occurred for the H3 SiCN⋯CX2 systems. Our analyses also show a large contribution made by the deformation energy to the tetrel bond and all of the pnicogen bonds displaying the closed shell characteristics of the weak interactions, as well as most of the tetrel bonds having partially covalent character, consistent with the remarkable induced dipole interaction between the two monomers. For the tetrel-bonded complexes, the polarization energies were found to exhibit a polynomial dependence on the change of the dihedral angle of the SiH3 fragment and the increase of integral charge in the Si⋯C internuclear region.